Infiltrative-Suppurative Form of Scalp Microsporia in a Child with Generalized Pustular Psoriasis of von Zumbusch: Clinical Case - Andrey L. Bakulev; Sergey S. Kravchenya; Irina A. Igonina ("Paediatrician" Publishers LLC, 2021)
Background. This article discusses issues of diagnosis and management of pustular psoriasis in a child associated with recurrent dermatomycosis, immunopathogenetic mechanisms of pustular psoriasis, its course and prognosis. Clinical Case Description. The clinical case of infiltrative-suppurative form of scalp microsporia in 11 years old child with long-term psoriasis vulgaris and its transformation to generalized pustular psoriasis (von Zumbusch) is described. The need of immunosuppressive therapy prescription for severe psoriasis was challenged with fungal skin infection as immune suppression would lead to its recurrent course. Conclusion. Combination treatment (systemic glucocorticosteroids, methotrexate, antibiotics, and griseofulvin) resulted in clinical and laboratory recovery for microsporia in a child with generalized pustular psoriasis.